Advances in the clinical management of high‐risk Wilms tumors. Issue 3 (10th January 2023) - Ortiz, Michael V.; Koenig, Christa; Armstrong, Amy E.; Brok, Jesper; de Camargo, Beatriz; Mavinkurve‐Groothuis, Annelies M. C.; Herrera, Thelma B. Velasquez; Venkatramani, Rajkumar; Woods, Andrew D.; Dome, Jeffrey S.; Spreafico, Filippo
Abstract: Outcomes are excellent for the majority of patients with Wilms tumors (WT). However, there remain WT subgroups for which the survival rate is approximately 50% or lower. Acknowledging that the composition of this high‐risk group has changed over time reflecting improvements in therapy, we introduce the authors' view of the historical and current approach to the classification and treatment of high‐risk WT. For this review, we consider high‐risk WT to include patients with newly diagnosed metastatic blastemal‐type or diffuse anaplastic histology, those who relapse after having been initially treated with three or more different chemotherapeutics, or those who relapse more than once. In certain low‐ or low middle‐income settings, socio‐economic factors expand the definition of what constitutes a high‐risk WT. As conventional therapies are inadequate to cure the majority of high‐risk WT patients, advancement of laboratory and early‐phase clinical investigations to identify active agents is urgently needed.